Hardware-Software Design of a Smart Sensor for Fully-Electronic DNA Hybridization Detection - Stagni, Claudio; Guiducci, Carlotta; Lanzoni, Massimo; Benini, Luca; Ricco, Bruno (Design, Automation and Test in Europe, 2005)
This paper describes the design of a smart sensor for label-free detection of DNA hybridization. The sensor is based on a direct electrical transduction principle: it measures impedance variation at the interface between a bio-functionalized electrode and a solution containing the analyte. The smart sensor includes a complete signal conditioning and processing subsystem based on an embedded μ-controller. We outline the sensor architecture, and we describe in details board-level integration as well as hardware and software implementation and design choices. The accuracy of our embedded solution has been evaluated by comparing it with a high-cost laboratory setup. Moreover, we provide measurements of real sensing structures which demonstrate in field the functionality of our system.